RELATIONSHIP OF SERUM ADIPONECTIN LEVELS WITH GLYCAEMIC STATUS IN PREGNANT WOMEN - Akhtar , Yasmin; Nawaz, Shah; Khan, Muhammad Shabbir; Habib, Syed Hamid; Malik, Muhammad Omar; Fatima, Sadia (Journal of Ayub Medical College Abbottabad, 2022)
Background: Adiponectin plays an important role in glucose metabolism and released in response to insulin. It helps to decrease glucose levels and insulin resistance; however, this relation is not been studied in pregnant ladies. Objective was to determine serum adiponectin level and glycaemic status in pregnant women belonging to Peshawar, Khyber Pakhtunkhwa (KPK) and to find any possible relationship between them. Methods: Hundred pregnant women with gestational diabetes mellitus (GDM) and 100 healthy pregnant women without GDM were randomly selected in a cross-sectional study. After an overnight fast, their blood samples were taken for determination of serum adiponectin, glycosylated haemoglobin (HbA1c) and fasting blood glucose (FBG). The relationship of adiponectin with glycaemic status was determined with Pearson Correlations coefficient (r). Results: Pregnant women with GDM when compared to healthy pregnant women showed significantly low levels of serum adiponectin (µg/mL) (2.2±0.2 vs. 11.25±4.8, p<0.05) and significantly high level of FBG (mg/dl) (182.7±64.2 vs. 93.6±5.9, p<0.05) and HbA1c (%) (7.4±0.1 vs. 5.4±0.1, p<0.05). Serum adiponectin level showed a statistically significant negative correlation with FBG (r = -0.203, p=0.042) and HbA1c (r = -0.744, p=0.000) in pregnant women with GDM. Conclusion: Serum adiponectin concentration is markedly decreased in pregnant women with GDM which concludes that Hypoadiponectinemia is related with deranged (elevated) glycaemic status in pregnancy. Moreover, adiponectin is associated negatively with FBG and HbA1c in the studied population.